BELAJAR CERIA, CINTA BUDAYA: PENGENALAN KEARIFAN LOKAL KALIMANTAN SELATAN MELALUI PERMAINAN TRADISIONAL UNTUK SISWA DI SDN SUNGAI LULUT 8 BANJARMASIN - Lili Agustina; Isna Kasmilawati; Nana Citrawati Lestari (STAI Darul Qalam Tangerang, 2026)
This Community Service activity aims to introduce the local wisdom of South Kalimantan to elementary school students through traditional games. Traditional games were chosen as a learning medium because they are familiar to children and rich in cultural values and character. This activity was carried out at SDN Sungai Lulut 8 Banjarmasin as an effort to foster a love of culture from an early age through fun and meaningful learning. The activity was carried out in several stages, namely socialization, discussion, simulation, practice, and reflection. Students were introduced to the games Tebak Flora–Fauna Kalimantan Selatan, Cuk Cuk Bimbi, and Besasahan, which were designed according to the characteristics of elementary school students. Each stage of the activity encouraged active student participation and provided a fun and participatory learning experience. The results of the activity showed an increase in student enthusiasm and participation during the learning process. Traditional games helped students understand the values of cooperation, sportsmanship, togetherness, and concern for local culture. This PKM activity is expected to become an alternative to local wisdom-based learning and contribute to the preservation of Banjar culture through education.